Analysis of Factors That Influence Bullying Behavior in Adolescents in Public Middle School in East Jakarta Region - Amin, Ade Nuriah; Supartini, Yupi; Tambunan, Eviana Sumarti; Sulastri, Titi; Ningsih, Ratna; Hapsari, Dina Carolina (Jurnal Keperawatan, 2024)
Bullying is intentional aggressive behavior by a stronger individual or group of peers against a weaker individual or group of peers, whether physically, verbally, or psychologically. This behavior occurs repeatedly and has a negative impact on the victim. The discussion in this research that will be examined are the factors that influence bullying behavior, including: age, gender, parents' educational background, parents' parenting patterns, and peer factors. This research was conducted to determine the factors that influence bullying behavior among teenagers at State Middle Schools in the East Jakarta Region. This type of research is quantitative correlation research with a cross sectional approach and the sampling technique in the research was carried out using non-random sampling with a purposive sampling technique. The sample size in this study was 115 respondents and was analyzed using the chi square test for bivariate and univariate analysis. Based on the results of the analysis, there is a relationship between parental parenting factors and bullying behavior (p value 0.014), and peer factors (p value 0.006) and bullying behavior. Based on the research results from the data presentation and discussion as described in the previous chapter, the results of this research explain based on the characteristics of the respondents (age, gender, and educational background of parents) which are of particular concern regarding internal factors that can be formed in the family to pay attention to each age stage of their child's development.